System Approach and Implementation of the Education Programme in Kenya - Mwaura, John; Gikonyo, Naomi; Kanjugu, John (Academia Kenya, 2021)
Education policy in Kenya, has been under review through various commissions since independence. Nevertheless, none of these attempts have provided a panacea to issues and challenges facing the education system. Sessional Paper Number 1 of 2005, recommended a Sectoral Wide Approach Planning, focusing on access, equity, quality, retention, and completion rates both at the primary and secondary level of education (MOEST, 2005). Though the approach is referred to as sectoral-wide, the policies focused more on two levels of education, disregarding early childhood and university.
Keywords: Education; Kenya